Monocyte adhesion to atherosclerotic matrix proteins is enhanced by Asn-Gly-Arg deamidation - Dutta, Bamaprasad (2018)
Atherosclerosis arises from leukocyte infiltration and thickening of the artery walls and constitutes a major component of vascular disease pathology, but the molecular events underpinning this process are not fully understood. Proteins containing an Asn-Gly-Arg (NGR) motif readily undergo deamidation of asparagine to generate isoDGR structures that bind to integrin αvβ3 on circulating leukocytes. Here we report the identification of isoDGR motifs in human atherosclerotic plaque components including extracellular matrix (ECM) proteins fibronectin and tenascin C, which have been strongly implicated in human atherosclerosis. We further demonstrate that deamidation of NGR motifs in fibronectin and tenascin C leads to increased adhesion of the monocytic cell line U937 and enhanced binding of primary human monocytes, except in the presence of a αvβ3-blocking antibody or the αv-selective inhibitor cilengitide. In contrast, under the same deamidating conditions monocyte-macrophages displayed only weak binding to the alternative ECM component vitronectin which lacks NGR motifs. Together, these findings confirm a critical role for isoDGR motifs in mediating leukocyte adhesion to the ECM via integrin αvβ3 and suggest that protein deamidation may promote the pathological progression of human atherosclerosis by enhancing monocyte recruitment to developing plaques.